2019
DOI: 10.1016/j.rmed.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A mesh nebulizer is more effective than jet nebulizer to nebulize bronchodilators during non-invasive ventilation of subjects with COPD: A randomized controlled trial with radiolabeled aerosols

Abstract: Background: Beneficial effects from non-invasive ventilation (NIV) in acute COPD are well-established, but the impact of nebulization during NIV has not been well described. Aim: To compare pulmonary deposition and distribution across regions of interest with administration of radiolabeled aerosols generated by vibrating mesh nebulizers (VMN) and jet nebulizer (JN) during NIV. Methods: A crossover single dose study involving 9 stable subjects with moderate to severe COPD randomly allocated to receive aerosol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
2
29
0
3
Order By: Relevance
“…In this study, there were only small differences between NIV and IMV with respect to the delivered aerosol dose (19.02% versus 22.64% respectively). Again, these figures are in line with previous published reports [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there were only small differences between NIV and IMV with respect to the delivered aerosol dose (19.02% versus 22.64% respectively). Again, these figures are in line with previous published reports [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…More recently, G alindo- F ilho et al [ 32 ], comparing the delivery of radiolabelled aerosol during NIV with jet and mesh nebulisers in moderate-to-severe COPD, patient-reported lung doses of 3.14% with a jet nebuliser versus 12.05% with a mesh nebuliser. Their lower reported lung dose than our in vitro reports is probably due to our use of collecting filters that are known to overestimate inhaled dose, and filters do not allow for exhalation of aerosol that occurs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of LAMA with LABA therapies has proven effective in COPD treatment, several studies showed their efficacy with inhalers [190,193] so delivery by nebulizer may soon be standard. There are also several clinical trials comparing JN versus VMN in COPD patients with some publications already pointing to preference for VMN [194]. Interestingly, the need for improved patient-orientated personalized care [195], and better adherence to prescription guidelines for asthma patients is also noted.…”
Section: Short-and Long-acting Adrenergic and Muscarinic Agonistsmentioning
confidence: 99%